Benznidazole biotransformation in rat heart microsomal fraction without observable ultrastructural alterations: comparison to Nifurtimox-induced cardiac effects - Montalto, Maria (2008)
Benznidazole (Bz) and Nifurtimox (Nfx) have been used to treat Chagas’ disease. Recent studies evidenced cardiotoxic effects of Nfx. We attempted to test whether Bz behaves similarly. Bz reached heart tissue of male rats after intragastric administration. No cytosolic Bz nitroreductases were detected, while a microsomal NADPH dependent Bz nitroreductase activity was found, which was mediated by P450 reductase. No ultrastructurally observable Bz deleterious effects were detected, in contrast to the cardiac effects previously reported for Nfx. As conclusion, if these drugs were used in chagasic patients, Bz would be less risky to heart function than Nfx, when any cardiopathy is present.